2008
DOI: 10.1103/physrevb.78.024506
|View full text |Cite
|
Sign up to set email alerts
|

Quantum interference and weak localization effects in the interlayer magnetoresistance of layered metals

Abstract: Studies of angle-dependent magnetoresistance oscillations ͑AMRO͒ in the interlayer conductivity of layered metals have generally considered semiclassical electron transport. We consider a quantum correction to the semiclassical conductivity that arises from what can be described as an interlayer Cooperon. This correction depends on both the disorder potential within a layer and the correlations of the disorder potential between layers. We compare our results with existing experimental data on organic charge-tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The present compound shows that the peak width clearly decreases with increasing magnetic field, and that the magnetoresistance at approximately θ = 90 • is scaled by B cos θ Kennett and McKenzie have proposed a new model for the 90 • peak in the angulardependent magnetoresistance [18]. They have considered quantum correction to the semiclassical conductivity in the incoherent layered system, and found that the 90 • peak appears owing to the weak localization effect.…”
mentioning
confidence: 60%
“…The present compound shows that the peak width clearly decreases with increasing magnetic field, and that the magnetoresistance at approximately θ = 90 • is scaled by B cos θ Kennett and McKenzie have proposed a new model for the 90 • peak in the angulardependent magnetoresistance [18]. They have considered quantum correction to the semiclassical conductivity in the incoherent layered system, and found that the 90 • peak appears owing to the weak localization effect.…”
mentioning
confidence: 60%
“…It should be emphasized that the model calculation above is too simplistic to be directly applied to the interlayer resistivity data mentioned in this section. (There are certain low-dimensional organic metals, with a multilayered structure and single-layer Fermi surfaces that are rotated with respect to each other, for which this model is more suitable [26][27][28] (see footnote 1).) The main point of this paper is that the semiclassical magnetotransport in a system composed of inequivalent, weakly coupled layers with discrete Fermi surface intersections is qualitatively distinctive.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the model captures the essential physics and properties (i), (ii) and (iii) above are predicted for generic multilayer systems. (I discuss the connection between the model calculation and existing experimental data near the end of the paper, see also 1 [26][27][28].) The advantage of considering a particular simplified model of a bilayer metal is that analytic expressions that provide insight into the key properties are readily obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,27,30 The only difference in AMRO for the two models of transport occurs for angles near θ = π 2 . 1,27,30,32 In order to make analytic progress with Eq. ( 16) we need to specify the energy and φ dependence of various Fermi surface properties.…”
Section: B Anisotropic Fermi Surfacementioning
confidence: 99%